2002
DOI: 10.1007/pl00012458
|View full text |Cite
|
Sign up to set email alerts
|

Weak subnormality of operators

Abstract: We consider the gap between weak subnormality and 2-hyponormality for Toeplitz operators. In addition, we study the spectrum of the minimal partially normal extension of a weakly subnormal operator, and the inverse of an invertible weakly subnormal operator. Introduction.In [15], the notion of weak subnormality of an operator was introduced as a generalization of subnormality, with an aim at providing a model for 2-hyponormal operators. Weak subnormality was conceived as a notion at least as strong as hyponorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…which will be called the n-th minimal partially normal extension of T. It was ( [10], [11], [13]) shown that 2-hyponormal =⇒ weakly subnormal =⇒ hyponormal and the converses of both implications are not true in general. It was [13]…”
Section: The Main Resultsmentioning
confidence: 99%
“…which will be called the n-th minimal partially normal extension of T. It was ( [10], [11], [13]) shown that 2-hyponormal =⇒ weakly subnormal =⇒ hyponormal and the converses of both implications are not true in general. It was [13]…”
Section: The Main Resultsmentioning
confidence: 99%